Prophetic Sexology in Hadith: A Preventive Model for Adolescent Counseling in Indonesia - Ubaidillah Hasan; Nurul Hidayat; Ahmad Saddad (Dialogia, 2025)
This study focuses on explaining the model of preventing sexual violence and crime by formulating religious values from thematic hadith texts sexology preventive counseling, as the basis of moral ideas in the relationship between men and women. This study aims to provide an overview of how sexology hadith texts can be used as prophetic counseling materials related to preventive sexology for adolescents. The method used in this study is content analysis using sexology theories about sex and sexuality in the structuring of sexology thematic hadith. As a result, the hadith texts that have the content of preventive sexology counseling for adolescents are not limited to sex as reproduction and procreation but transcendent and ecosexological. Second, prophetic sexology provides biological (al-jismiyyah), psychological (an-nafsiyyah), spiritual (ar-rūhāniyyah), and ecological (al-bī'ah) aspects. Third, the value of preventive sexology of counseling on the aspect of al jismiyyah strengthens in terms of hygiene and health of the reproductive organs (at-tahārah) and marriage commitment. Meanwhile, the al-nafsiyyah aspect emphasizes productive and safe attitudes, behaviors, sexual urges and sexual orientations as well as humanist gender relations. Meanwhile, the aspect of al-bī'ah emphasizes the urgency of sexuality related to the function of vital organs that are actively involved in protecting the environment as well as the spiritual aspects of al-ruhaniyyah which reflects the cleanliness of the heart (rūhiyyah) from immoral behavior or adultery.  An Important contribution of this studi is the basic idea of prophetic sexology goes beyond sexual health, reproduction, and procreation, namely, sacredness, spirituality, and ecology adolescent sexual healt counselling. Contributions that can be made by sexology counseling include increasing awareness about reproductive health and self-esteem (al-‘iffah), maintaining modesty (al-hayā'), and paying attention to aspects of eco-sexology and spiritual sexology. REFERENCES Abu Abdullah Muhammad bin Ismail al-Bukhari. Sahih Al-Bukhari. Edited by Musthafa Dib Al-Bagha. Damaskus: Dar Ibnu Katsir, 1993. Abu al-Abbas Ahmad bin Umar bin Ibrahim al-Qurtubi. Al-Mufahim Al-Mashkal Al-Mujtahid Al-Kitab Al-Muslim. Damaskus: Dar Ibnu Katsir, 1996. Abu al-Abbas al-Qurtubi Zia al-Din Ahmad. Takhrij Sahih Al-Bukhari Wa Bayan Al-Gharibah. Edited by Rifaat Fawzi Abdul Muthalib. Damaskus: Dar al-Naufal, 2014. Abu al-Hussein Muslim bin al-Hajjaj bin Muslim. Sahih Muslim. Edited by Muhammad Fuad Abd Al-Baqi. Kairo-Mesir: Issa al-Babi al-Halabi, 1953. Abu Dawud Sulaiman bin al-Asy’as. Sunan Abu Dawud. Edited by Muhammad Muhyiddin Abd Al-Hamid. Beirut: al-Maktabah al-Asiriyah, n.d. Ahmad. “Kekerasan Seksual Pada Anak-Anak Di Berbagai Wilayah Meningkat, Internet Jadi Pemicu.” Hidayatullah.com, 2024. https://hidayatullah.com/berita/2024/01/24/266611/kekerasan-seksual-pada-anak-anak-di-berbagai-wilayah-indonesia-meningkat.html. Ahmad Muhammad Diponegoro. Psikologi Dan Konseling Qur’ani. Yogyakarta: Multi Presindo, 2014. Ahmed, Sameera, and Mona M. Amer, eds. Counseling Muslims: Handbook of Mental Health Issues and Interventions. United States of America: Taylor & Francis, 2013. Al-Baydawi, Nasiruddin Abdullah bin Umar. Tahfat Al-Abrar Syarh} Mus}ah}ih Al-Sunnah. Edited by Nuruddin Thalib. Kuwait: Kementrian Wakaf dan Urusan Agama Islam, 2012. Al-Bukhari, Abu Abdullah Muhammad bin Ismail. Sahih Al-Bukhari. Kairo-Mesir: Dar al-Tsaqafah, 2012. Al-Fasi, Ibnul Qattan. Ihkam Al-Nazar. Edited by Idris Al-Samadi. Damaskus: Darul Qalam, 2012. Al-Manawi, Abu al-Mundzir Mahmud bin Muhammad bin Musthafa bin Abd al-Latif. Al-Tahrir Syarh Al-Dalil. Mesir: Al-Maktabah al-Syamilah, 2011. Al-Qasim, Ahmad bin Muhammad bin Manshur bin, and Nasir al-Din bin al-Munir Al-Sakandari. Al-Matwari. Edited by Salahuddin Maqbul Ahmad. Kuwait: Pustaka Al-Mualla, 2010. Al-Saati, Abd al-Rahman bin Muhammad al-Banna, and Al-Fath Al-Rubani. Syarh Musnad Imam Ahmad Bin Hanbal Al-Syaibani. Riyadh: Dar al-Rahiya al-Hadits al Arabi, n.d. Ali, Kecia. Sexual Ethics And Islam. Oxford: Oneworld Publication, 2006. Amanda, Clara, and Ade Adhari. “Pentingnya Pendidikan Seksualitas Dalam Mencegah Kekerasan Seksual Terhadap Perempuan.” Ranah Research : Journal of Multidisciplinary Research and Development 7, no. 1 (2024): 677–86. https://doi.org/https://doi.org/10.38035/rrj.v7i1.1303. As-Subkiy, Mahmud Muhammad Khathab. Ad-Din Al-Khalis Au Irsyad Al-Khalq Ila Din Al-Haq. Edited by Amin Mahmud Khathab. Riyadh: al-Maktabah al-Mahmudiyah as-Subkiyah, 1976. As-Sunaiki, Zakaria bin Muhammad bin Ahmad bin Zakaria al-Anshari. Minhah Al-Bari Bi Syarah Sahih Bukhari Al-Musami. Edited by Sulaiman Ibn Dari’i Al-’Azami. Riyadh: Maktabah Rasyid Linnasyir Wa at-Tauzii’, 2005. At-Tamimi, Abu ’Abdullah Muhammad bin Shalih bin Muhammad bin Sulaiman bin Abdur Rahman Al-’Utsaimin. Fathu Zi Al-Jalali Wa Al-Ikram Bi Syarah Bulughul Maram. Edited by Shubhi Ibn Muhammad Ramadhan. Riyadh: al-Maktabah al-Islamiyyah Linnasyir Wa at-Tauzii’, 2006. At-Tirmidzi, Abu Isa Muhammad Ibn Isa. Sunan Tirmidzi. Edited by Ahmad Muhammad Syakir, Muhammad Fuad Abdul Baqi, and Ibrahim ’athwah ’audh. Mesir: yirkah Maktabah Wa Matba’ah Musthafa al-Bab al-Halabi, 1974. Bonnefoit, Régine, Melissa Rérat, and Samuel Schellenberg, eds. New Media in Art History: Tensions, Exchanges, Situations. De Gruyter, 2023. Dliyauddin, Abu al-’Abbas al-Qurthubi. Ikhtisar Sahih Bukhari Wa Bayanu Gharibuhu. Edited by Rif’at Fauzi Abdul Muthallib. Damascus: Dar an-Nawadir, 1435. Duderija, Adis, and Ghulam Rasool. “Bilal Philips as a Proponent of Neo-Traditional Salafism and His Significance for Understanding Salafism in the West.” Religions 2019, Vol. 10, Page 371 10, no. 6 (June 5, 2019): 371. https://doi.org/10.3390/REL10060371. Hanbal, Ahmad bin Muhammad bin. Musnad Al-Imam Ah}mad Bin Hanbal. Edited by Ahmad Muhammad Shakir. Kairo: Dar al-Hadis, 1995. Hasan. “Seksologi Al Qur’an.” Dialogia 1, no. 2 (2021): 12–13. https://doi.org/https://doi.org/10.21154/dialogia.v20i1.3791. Hasan, Ubaidillah. “Darurat Seksologi; Pendidikan Seksual Preventif Sebagai Kesadaran Kritis Perspektif Al-Quran.” Dialogia: Jurnal Studi Islam Dan Sosial 18, no. 2 (2020): 443–65. https://doi.org/DOI: https://doi.org/10.21154/dialogia.v18i2.2304. ———. “Theo-Sexology in The Quran as A Strategy for Family Resilience of Migrant Workers in Indonesia.” Dialogia 22, no. 2 (December 30, 2024): 197–217. https://doi.org/10.21154/DIALOGIA.V22I2.8780. Hasan, Ubaidillah, and Robitoh Widiastutik. “Theo-Sexology In The Qur’anic Exegesis: A Strategy For Family Resilience Of Migrant Workers In Indonesia.” Al-Bayan: Jurnal Studi Ilmu Al- Qur’an Dan Tafsir 9, no. 2 (2024): 1–14. https://doi.org/DOI: https://doi.org/10.15575/al-bayan.v9i1.37161. Hayat, Abdul. Konsep Konseling Berdasarkan Ayat-Ayat Al Qur’an. Yogyakarta: LKiS Yogyakarta, 2016. Ibn Mulaqin Sirojuddin Abu Hafsh. Al-Badru Al-Munir Fi Takhrij Al-Ahadits Wa Al-Asar Al-Waqa’ah Fi Asy-Syarah Al-Kabir. Edited by Musthhofa Abu Al-Ghaith. Riyadh: Dar al-Hijrah Linnasyir Wa at-Tauzii’, 1425. Irianto, Koes. Memahami Seksologi. Bandung: Sinar Baru Algesindo, 2010. Jawazi, Jamaluddin Abu al-Faraj Abdurrahman Al. Kasyaf Al-Musykil Min Hadis as-Sahihain. Edited by Ali Husain Al-Bawab. Riyadh: Dar al-Wathan, n.d. Khalaf, Ibn Bathal Abu al-Hasan Ali Ibn. Syarah Sahih Bukhari Li Ibn Bathal. Edited by Abu Tamiim Yaasir Ibn Ibrahim. Riyadh: Maktabah Rasyid as-Sa’udiyah, 2003. Laili, Rifqi As’adah, Ubaidillah Hasan, and Siti Marpuah. “Sarungan Sexology: Exploring the Moral Ideas of the Qurán as an Effort to Prevent Sexual Violence in Pesantren.” Islamika Inside: Jurnal Keislaman Dan Humaniora 11, no. 1 (June 26, 2025): 1–21. https://doi.org/10.35719/ISLAMIKAINSIDE.V11I1.278. Ma’ruf, Bashar Awwad, al-Sayyid Abu al-Maati Al-Nuri, Muhammad Mahdi Al-Muslimi, and Ahmad Abd al-Razzaq Eid Ayman Ibrahim al-Zamil Mahmud Muhammad Khalil. Al Musnad. Dar al-Gharb al-Islami, 2013. Maa, Fini La, Abdul Mutalib, and Abu Sahman Nasim. “Perbudakan Modern Di Arab Saudi: Seksualitas Majikan Dan Budak Perempuan Di Zaman Jahiliyah.” Indonesian Journal of Shariah and Justice 4, no. 1 (2024): 83–108. https://doi.org/DOI: https://doi.org/10.46339/ijsj.v4i1.79. Mahmud Yunus Mustofa and Firmanda Taufiq. “Islamic Feminism: Discourse on Gender and Sexuality in Contemporary Islam.” Gender, Place & Culture, 31, no. 3 (2023): 408–411. https://doi.org/https://doi.org/10.1080/0966369X.2023.2270268. Majd al-Din Abu al-Sa’adat al-Mubarak. Jami’ Al-Sunnah Al-Kubra. Edited by Abd al-Qadir Al-Arnaout. Pustaka al-Hilwani, 1970. Muammar. “Gender, Sexuality and Islam in Contemporary Indonesia: Queer Muslims and Their Allies.” International Feminist Journal of Politics, 2025, 234. https://doi.org/https://doi.org/10.1080/14616742.2024.2441342. Muhammad Ishaq Muhammad Ibrahim. Kasyf Al-Manajah Wa Al-Tanakih Fi Takhrij Al-Mubahij. Beirut, 2004. Munawaroh, Safitri, Ariesta Putri Wijaya, Izzatun Nafis, Imelda Patricia, Rahma Putri Widiyanti, Faizal Ardiansyah, and Muhardila Fauziah. “Pentingnya Penerapan Sex Education Dalam Upaya Pencegahan Pelecehan Seksual Terhadap Anak Sekolah Dasar.” Urnal Basicedu 8, no. 1 (2024): 747–761. https://doi.org/https://doi.org/10.31004/basicedu.v8i1.7171. Muslim, Abu al-Husain Muslim ibn al-Hajjaj ibn. Sahih Muslim. Turki: Dar al-Taba’a al-Amra, 1913. Muslimah. “17 Siswa Jadi Korban Perilaku Seks Menyimpang Oknum Guru Ini, Terbongkar Setelah Ada Yang Curhat.” Tribun Jatim.com, 2024. https://jateng.tribunnews.com/2024/01/30/17-siswa-jadi-korban-perilaku-seks-menyimpang-oknum-guru-ini-terbongkar-setelah-ada-yang-curhat?lgn_method=google. Naisabūrī, Abu al Husain Muslim bin al Hajjaj bin Muslim bin Ward bin Kūsyāż al qusyairi al. Sahih Muslim. Edited by Muhammad Dzihni Afandi. Turki: Dar at-Thaba’ah al-’Amirah, 1334. Neves, Silva. Sexology: The Basics. Taman Milton, Abingdon, Oxon: Routledge, 2023. Pardi, Pardi, Dimas Indiarto S, Yusro Edy Nugroho, Sri Haryatmo, Dian Susilastri, and Sutejo Sutejo. “The Influence of Islam on Sex Education in The Serat Centhini.” In Proceedings of the Saizu International Conference on Transdisciplinary Religious Studies, 245–254. Purwokerto: International Office UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2024. https://doi.org/DOI: https://doi.org/10.24090/icontrees.2024.1193. Riyani, Irma. Islam, Women’s Sexuality and Patriarchy in Indonesia. London and New York: Routledge, 2020. Science, Between. Histories of Sexology, n.d. Serour, G. I. “Ethical Issues in Human Reproduction: Islamic Perspectives.” Gynecological Endocrinology 29, no. 11 (November 2013): 949–52. https://doi.org/10.3109/09513590.2013.825714;CTYPE:STRING:JOURNAL. Sharaf al-Din al-Hussein bin Abdullah al-Tibi. Syarh} Misykat Al-Mubah}ih}. Edited by Abdul Hamid Hindawi. Riyadh: Pustaka Nizar Musthafa al-Baz, 1996. Siregar, Elizabeth, Dessy Rakhmawaty, and Zulham Adamy Siregar. “Kekerasan Seksual Terhadap Perempuan: Realitas Dan Hukum.” PROGRESIF: Jurnal Hukum 4, no. 1 (2020): 1–14. https://doi.org/DOI: https://doi.org/10.33019/progresif.v14i1.1778. Sirri, Lana. Islamic Feminism Discourses on Gender and Sexuality in Contemporary Islam. New York: Routledge, 2021. Syafaruddin. Bimbingan & Konseling: Perspektif Al-Quran Dan Sains. Edited by Syafaruddin, Ahmad Syukri Sitorus, and Ahmad Syarqawi. 1st ed. Medan: Perdana Publishing, 2017. Umar, Siraj al-Din Abu Ḥafṣ. Al-Taḥyah Syarh Al-Jami’ Al-Shahīḥ. Damaskus: Dar al-Nauḍir, 2008. Wajdi, Farid, and Asmani Arif. “Pentingnya Pendidikan Seks Bagi Anak Sebagai Upaya Pemahaman Dan Menghindari Pencegahan Kekerasan Maupun Kejahatan Seksual.” Jurnal Abdimas Indonesia 1, no. 3 (2021): 129-137. https://doi.org/https://doi.org/10.53769/jai.v1i3.130. Zubairi, Furhan, Jamal Ahmed Bashier Badi, and Mohammad Eisa Ruhullah. “Quranic Analysis: A Critical Examination of Gender in Islamic and Western Paradigms.” MAQOLAT: Journal of Islamic Studies 2, no. 2 (2024): 70–86. https://doi.org/DOI: https://doi.org/10.58355/maqolat.v2i2.67.